The ERM Complex: A New Player Involved in Diabetes-induced Vascular Leakage - Simó-Servat, Olga; Hernández, Cristina; Simó, Rafael (Current Medicinal Chemistry, 2020)
Background: Microvascular complications remain an important cause of morbidity in diabetic patients, and they are associated with a significant economic burden for healthcare systems. Vascular leakage is one of the earlier hallmarks in diabetic microvascular complications. Ezrin, Radixin and Moesin (ERM) proteins have recently been involved in vascular dysfunction under the effect of molecular mediators of diabetes complications. In this review, we will present the available evidence regarding the role of these proteins in vascular leakage and their putative implication in diabetic microvascular complications. Methods and Results: A comprehensive literature search of the electronic MEDLINE database was performed between November 2017 and January 2018. As a result, 36 articles have been reviewed and discussed. Discussion: ERM proteins are cytoskeleton-membrane linkers, and when activated in endothelial cells are able to induce cytoskeleton reorganization in stress fibers leading to the disassembly of focal adhesions and the formation of paracellular gaps which result in an increase of vascular permeability. The activation of these proteins is induced by mediators involved in diabetic complications such as PKC activation, TNF-α, AGEs and oxidative stress. In conclusion, ERMs play an essential role in endothelium homeostasis and can be envisaged as a new therapeutic molecular target for preventing or arresting diabetes-induced vascular leakage.
Keywords: diabetes-induced vascular leakage